Mode-Voltage Constrained Control for Adaptive Optics System - Ruitao Wang; Youming Guo; Nanfei Yan; Ying Yang; Lanqiang Zhang; Qiong Tu; Lingxiao Li; Changhui Rao (IEEE Photonics Journal, 2024)
In the adaptive optics system of astronomical observation, the deformable mirror and the tip/tilt mirror are coupled during the correction process. However, due to the limited sensitivity of the Shack-Hartmann wavefront sensor in detecting piston aberration, it becomes necessary to constrain piston aberration caused by the deformable mirror. This paper introduces a straightforward and efficient decoupling control algorithm that is based on mode-voltage constraints. The proposed algorithm utilizes the mode method to decompose the control voltage mode, constructs a transition matrix to avoid piston and tip/tilt aberrations, and combines this matrix with the response matrix of the deformable mirror to generate a new reconstruction matrix. The direct slope algorithm is used to obtain the mode coefficient of the control voltage, which is then followed by obtaining the constrained control voltage through the proportional-integral controller and transition matrix. Simulation results demonstrate that this algorithm outperforms both the traditional vector project-constraint algorithm and the projection-based decoupling algorithm. The experimental results demonstrate the effective suppression of coupling between the deformable mirror and tip/tilt mirror by this algorithm, leading to a higher Strehl Ratio and improved correction for first 44-order Zernike mode aberrations.